2011
DOI: 10.1158/0008-5472.can-10-3689
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Class II–Associated Invariant Chain Peptide on Leukemic Blasts of Patients Promotes Activation of Autologous Leukemia-Reactive CD4+ T Cells

Abstract: Immune escape in cancer poses a substantial obstacle to successful cancer immunotherapy. Multiple defects in HLA class I antigen presentation exist in cancer that may contribute to immune escape, but less is known about roles for HLA class II antigen presentation. On class II þ leukemic blasts, the presence of class II-associated invariant chain peptide (CLIP) is known to be correlated with poor survival in acute myeloid leukemia (AML). In this study, we evaluated the functional significance of CLIP expression… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 42 publications
(35 reference statements)
0
17
0
Order By: Relevance
“…23,65,66 In contrast, some CLIP ¡ tumor cells were able to process li-independent endogeneous antigens generated by the proteasome for HLA class II-restricted presentation thereby activating TAA-specific CD4 C T cells. 23,67 Furthermore, it has recently been suggested that the different HLA class II phenotypes in tumors can be controlled at the post-transcriptional level, in particular by microRNAs (miRs). 42 Bioinformatic analyses have identified a number of miRs binding to the 3 0 -untranslated region (3 0 -UTR) of CIITA.…”
Section: Deregulation Of Hla Class II Apm Components In Malignant Cellsmentioning
confidence: 99%
“…23,65,66 In contrast, some CLIP ¡ tumor cells were able to process li-independent endogeneous antigens generated by the proteasome for HLA class II-restricted presentation thereby activating TAA-specific CD4 C T cells. 23,67 Furthermore, it has recently been suggested that the different HLA class II phenotypes in tumors can be controlled at the post-transcriptional level, in particular by microRNAs (miRs). 42 Bioinformatic analyses have identified a number of miRs binding to the 3 0 -untranslated region (3 0 -UTR) of CIITA.…”
Section: Deregulation Of Hla Class II Apm Components In Malignant Cellsmentioning
confidence: 99%
“…A small remnant of this protein, the class II-associated invariant chain peptide (CLIP), can be presented by HLA-DR complexes on the surface of leukemic blasts, resulting in decreased immunogenicity. 15 Interestingly, in APL cases, we observed that CLIP was abundantly expressed at the surface of HLA-DR-negative leukemic promyelocytes. Here, we studied the application of the analysis of CLIP expression in the discrimination of HLA-DRnegative AML subgroups, including APL, by flow cytometry.…”
mentioning
confidence: 70%
“…We have previously shown that leukemic cells expressing CLIP are poorly recognized by CD4C T helper cells. 5 Alternatively, we revealed that CLIP can also be presented by HLA class I, implicating that insufficient recognition by cytotoxic CD8C T cells might play a role as well. 6 Probably, genes regulating the antigen presentation pathway are impaired in leukemic cells, leading to increased expression of CLIP.…”
mentioning
confidence: 86%
“…5 In our recent study, we assessed whether CLIP on residual leukemic cells could add to the prognostic value of MRD frequency for relapse risk. 7 The current cutoff for MRD positivity is 0.1%.…”
mentioning
confidence: 99%